Analisis Proses Produksi dan Perhitungan Harga Pokok Produksi pada UKM Batagor ESQ - Khairunnisa, Firda; Salsabila, Shafa; Simangunsong, Levia Eclesia; Tartiani, Yuni Astuti Tri (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2024)
The owner of the Small and Medium Enterprises (SMEs) Batagor ESQ is located in Bogor, in the implementation of financial records still needs help. One of the impacts of SMEs that have financial records is that they can know and control the expected level of business profits. In accordance with the name of the business, this SME carries out activities to produce and sell battery products. The purpose of this study is to analyze the production process and calculate the cost of production of Batagor ESQ SMEs. The research was carried out through interviews with the owners to get clear information. In addition, this research was also carried out by surveying the Batagor ESQ SMEs. The results of the research on the calculation of the Cost of Production (HPP) were obtained with a unit price of IDR 5.000. The results obtained from the application of the financial literacy concept turned out to be enough to increase their business, so that finances became more structured and clear. With a total revenue of IDR 70,000,000 and production costs of IDR 18,731,000 for a period of one month. The profit margin obtained by Batagor ESQ SMEs is 73.24%.